Glued sponge as well as preparation process and application thereof

By immersing a colloid mixture of polyurethane hot melt glue and thermally expanded paraffin-based microspheres in the sponge, the problems of uneven distribution of colloids and volatilization of harmful gases in the leather and sponge composite process are solved, and an efficient and environmentally friendly composite effect is achieved.

CN120441911APending Publication Date: 2025-08-08JIANGSU KUANGDA AUTOMOTIVE TRIM CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510576496.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

In the prior art, the composite process of leather and sponge requires multiple processes, the colloid distribution is uneven, the bonding strength is insufficient, and harmful gases are evaporated, making it difficult to meet the requirements of green and environmental protection.

Method used

Immerse the colloidal mixture of polyurethane hot melt glue, thermally expanded paraffin-based microspheres and ethyl acetate in the sponge. The thermally expanded paraffin-based microspheres melt and lift the polyurethane hot melt glue to float on the sponge surface, firmly fit with the leather, simplify the process flow and reduce the volatility of harmful gases.

Benefits of technology

It realizes efficient and uniform composite of sponge and leather, simplifies the process flow, improves production efficiency, reduces environmental pollution, and ensures the flatness and bonding strength of the leather surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005388735590000071
    Figure BDA0005388735590000071
Patent Text Reader

Abstract

The invention discloses a sponge with glue and a preparation process and application thereof, and belongs to the technical field of sponges, the sponge with glue is characterized in that the sponge with glue comprises a polyurethane flexible foam sponge and a colloid mixture immersed in the polyurethane flexible foam sponge, the colloid mixture is composed of a polyurethane hot melt adhesive, thermal expansion paraffin-based microspheres and ethyl acetate, the weight ratio of the polyurethane hot melt adhesive to the ethyl acetate is 1: (2.3-2.7), the amount of the thermal expansion paraffin-based microspheres accounts for 5-10% of the total amount of the polyurethane hot melt adhesive and the ethyl acetate, the colloid mixture is immersed in the sponge, the colloid floats upwards after heating, and the sponge is formed. Therefore, high-efficiency and uniform compounding of the sponge and the leather is realized, an additional surface gluing or glue film compounding process is not needed, the production efficiency is improved, and the environmental pollution is also reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sponges, in particular to a sponge with adhesive, a preparation process and an application thereof. Background Art

[0002] Leather composite sponge refers to gluing a layer of sponge on the surface of leather to increase the softness and comfort of the leather. This process is often used in car seats, home decoration, footwear and other fields.

[0003] In the prior art, in order to achieve the composite of leather and sponge, PUR glue or hot melt adhesive film is usually directly applied or arranged on the sponge surface, and then bonding is achieved by heating and pressing. However, this method requires two steps: composite the glue with the sponge and then composite it with the leather. There are also problems such as uneven distribution of the colloid, insufficient bonding strength, and uneven flow of the colloid after heating, resulting in an uneven leather surface. In addition, the traditional glue coating process is often accompanied by the volatilization of toxic and harmful gases, which is harmful to human health and difficult to meet the requirements of green environmental protection. Summary of the Invention

[0004] In order to solve the problems in the prior art, the present invention provides a sponge with glue, a preparation process and application thereof, in which a colloid mixture is immersed in the sponge, and the colloid floats up after heating, thereby achieving efficient and uniform compounding of the sponge and leather. No additional surface coating or composite film process is required, thereby improving production efficiency and reducing environmental pollution.

[0005] The first aspect of the present invention is to provide a sponge with adhesive, which adopts the following technical solution: A sponge with adhesive, comprising a polyurethane soft foam sponge and a colloid mixture immersed in the polyurethane soft foam sponge, wherein the colloid mixture consists of polyurethane hot melt adhesive, heat-expandable paraffin-based microspheres and ethyl acetate, wherein the weight ratio of the polyurethane hot melt adhesive to the ethyl acetate is 1:(2.3-2.7), and the amount of the heat-expandable paraffin-based microspheres is 5-10% of the total amount of the polyurethane hot melt adhesive and the ethyl acetate.

[0006] By adopting the above-mentioned technical solution, the present application soaks a colloidal mixture consisting of polyurethane hot melt adhesive, heat-expandable paraffin-based microspheres and ethyl acetate in a polyurethane soft foam sponge, and then dries the sponge with adhesive and uses it. The leather and the polyurethane soft foam sponge are directly laminated and heated. At this time, the polyurethane hot melt adhesive and heat-expandable paraffin-based microspheres in the sponge with adhesive begin to melt, and the paraffin-based microspheres begin to expand after melting, lifting the polyurethane hot melt adhesive to move upward and float out of the sponge surface, thereby achieving a firm fit with the leather. This eliminates the need for an additional coating process, simplifies the composite process flow, and reduces the volatilization of harmful gases, in line with the concept of green environmental protection. In addition, after the sponge is immersed in the colloidal mixture, the fluidity of the colloidal mixture can be made more uniform during heating, effectively ensuring the flatness of the leather surface.

[0007] Preferably, the polyurethane hot melt adhesive is modified to obtain a modified polyurethane hot melt adhesive, and the modification method comprises the following steps: (1) Add dehydrated diisobutyl sebacate to the dry polyurethane hot melt adhesive at a temperature of 80 ± 2°C and mix and stir under vacuum for at least 30 minutes until no bubbles are generated; (2) lowering the temperature to 60±2°C, adding calcium carbonate, and continuing to stir under vacuum for not less than 30 minutes to obtain a blend; (3) Extruding the blend and drying it to obtain a modified polyurethane hot melt adhesive with a particle size of 1-20 μm.

[0008] Preferably, the amount of dehydrated diisobutyl sebacate added is 5-10 wt% of the weight of the polyurethane hot melt adhesive, and the amount of calcium carbonate added is 1-3 wt% of the weight of the blend obtained in step (1).

[0009] Preferably, the polyurethane hot melt adhesive in step (1) has a melting point of 70-100° C. and a particle size of 80-150 μm.

[0010] By adopting the above technical solution, when a polyurethane hot melt adhesive with a melting point between 70-100°C and a particle size between 80-150μm is selected, it can be effectively ensured that the polyurethane hot melt adhesive can be evenly penetrated into the sponge skeleton, and it also helps the polyurethane hot melt adhesive to flow evenly when heated; in addition, after the polyurethane hot melt adhesive is modified with dehydrated diisobutyl sebacate and calcium carbonate, the dispersion efficiency of the adhesive particles in the sponge skeleton can be effectively improved. At the same time, the introduction of calcium carbonate can improve the crystal structure of the polyurethane hot melt adhesive, thereby accelerating the melting-curing speed and improving the composite quality of the sponge and leather.

[0011] Preferably, the surface of the heat-expandable paraffin-based microspheres is coated with a silane coupling agent.

[0012] Preferably, the method for coating the surface of the heat-expandable paraffin-based microspheres with a silane coupling agent comprises the following steps: (1) Microsphere pretreatment: The heat-expandable paraffin-based microspheres were dispersed in anhydrous ethanol, ultrasonically cleaned, and then vacuum-dried at 40-45°C. (2) Preparation of an ethanol mixture: at room temperature, ethanol and water were mixed in a volume ratio of 9:1, KH-550 was added at 1-5% of the volume of the mixture, the pH value of the mixture was adjusted to 4-5, and the mixture was stirred for 1-2 hours to obtain a silane solution; (3) At room temperature, the heat-expandable paraffin-based microspheres and the silane solution were mixed in a weight ratio of 1:15 and stirred until the heat-expandable paraffin-based microspheres were completely suspended. The heat-expandable paraffin-based microspheres were then centrifuged and washed with ethanol. The heat-expandable paraffin-based microspheres were then vacuum-dried at 40°C to obtain the heat-expandable paraffin-based microspheres coated with the silane coupling agent.

[0013] By adopting the above technical solution, after the surface of the heat-expandable paraffin-based microspheres is coated with a silane coupling agent, the bonding force between the heat-expandable paraffin-based microspheres and the polyurethane hot melt adhesive is effectively improved, so that the heat-expandable paraffin-based microspheres can effectively support the polyurethane hot melt adhesive after heating. In addition, after the heat-expandable paraffin-based microspheres are coated with a silane coupling agent, the heat-expandable paraffin-based microspheres can also be effectively prevented from agglomerating, thereby improving the dispersion effect of the heat-expandable paraffin-based microspheres.

[0014] The second aspect of the present invention is to provide a process for preparing the adhesive sponge as described above, comprising the following steps: S1. Preparation of a colloid mixture: polyurethane hot melt adhesive and ethyl acetate are mixed by a twin-screw blending method at 50-70° C. for not less than 15 minutes, with a twin-screw speed of 5000 rpm or higher. After uniform mixing, heat-expandable paraffin-based microspheres are added, and stirring is continued at 50-70° C. and a twin-screw speed of 5000 rpm or higher for 10 minutes to obtain a colloid mixture; S2. Place the polyurethane soft foam sponge in a vacuum device and vacuum it for no less than 15 minutes; S3, completely immersing the polyurethane soft foam sponge obtained in step S2 in the colloid mixture obtained in step S1, with the immersion time being ≥ 20 min; S4, drying the impregnated sponge to obtain a sponge with glue.

[0015] Preferably, the vacuum degree in step S2 is not less than 0.1 MPa.

[0016] Preferably, the drying temperature in step S4 is 50±2°C.

[0017] The third aspect of the present invention is to provide an application of an adhesive sponge, which is to compound the adhesive sponge with leather, including the following steps: stacking the leather and the adhesive sponge, placing them in a compounding device with a pressure of 0.5 MPa for gradient heating, and the gradient heating process is: the first step is to heat to 80°C and preheat for 3 minutes, the second step is to heat to 100°C and maintain for 5 minutes, and the third step is to cool to 90°C and maintain for 2 minutes to bond the adhesive sponge to the leather to obtain a leather-sponge composite.

[0018] By adopting the above technical solution, the present application adopts a gradient heating method, which can effectively ensure that the colloidal mixture in the sponge melts evenly, thereby achieving uniform compounding of the leather and the sponge.

[0019] In summary, the present invention has the following beneficial effects: 1. In the present application, after a colloidal mixture consisting of polyurethane hot melt adhesive, heat-expandable paraffin-based microspheres and ethyl acetate is soaked in a polyurethane soft foam sponge, the sponge with adhesive is dried and used. The leather and the polyurethane soft foam sponge are directly laminated and heated. At this time, the polyurethane hot melt adhesive and the heat-expandable paraffin-based microspheres in the sponge with adhesive begin to melt. After melting, the paraffin-based microspheres begin to expand, lifting the polyurethane hot melt adhesive to move upward and float out of the sponge surface, thereby achieving a firm fit with the leather. This eliminates the need for an additional coating process, simplifies the composite process flow, and reduces the volatilization of harmful gases, in line with the concept of green environmental protection. In addition, after the sponge is immersed in the colloidal mixture, the fluidity of the colloidal mixture can be made more uniform during heating, effectively ensuring the flatness of the leather surface and improving production efficiency.

[0020] 2. This application not only improves the dispersion effect of the polyurethane hot melt adhesive and the heat-expandable paraffin-based microspheres in the sponge by modifying them separately, but also helps the colloid to flow evenly after being heated, thereby ensuring the composite quality of the sponge and leather. DETAILED DESCRIPTION

[0021] The present invention is further described in detail below with reference to the examples. All reagents without manufacturer's indication are conventional reagent products that can be obtained commercially.

[0022] Preparation Example 1.1 A method for modifying a polyurethane hot melt adhesive comprises the following steps: (1) At a temperature of 80 ± 2 ° C, a dry polyurethane hot melt adhesive (water content ≤ 0.05% (w / w)) with a melting point of 70-100 ° C and a particle size of 80-150 μm was selected, and 5 wt% of the weight of the polyurethane hot melt adhesive was added to the mixture, and the mixture was stirred under vacuum for 35 minutes until no bubbles were generated; (2) lowering the temperature to 60±2° C., adding 1 wt % of calcium carbonate based on the weight of the mixture obtained in step (1), and continuing to stir under vacuum for 30 min to obtain a blend; (3) Extruding the blend and drying it to obtain a modified polyurethane hot melt adhesive with a particle size of 1-20 μm.

[0023] Preparation Example 1.2 A method for modifying a polyurethane hot melt adhesive comprises the following steps: (1) At a temperature of 80 ± 2 ° C, a dry polyurethane hot melt adhesive (water content ≤ 0.05% (w / w)) with a melting point between 70 and 100 ° C and a particle size of 80-150 μm was selected, and dehydrated diisobutyl sebacate (10 wt% of the weight of the polyurethane hot melt adhesive) was added thereto, and the mixture was stirred under vacuum for 35 minutes until no bubbles were generated; (2) lowering the temperature to 60±2° C., adding 3 wt % of calcium carbonate based on the weight of the mixture obtained in step (1), and continuing to stir under vacuum for 35 min to obtain a blend; (3) Extruding the blend and drying it to obtain a modified polyurethane hot melt adhesive with a particle size of 1-20 μm.

[0024] Preparation Example 2.1 A method for coating the surface of heat-expandable paraffin-based microspheres with a silane coupling agent comprises the following steps: (1) Microsphere pretreatment: The heat-expandable paraffin-based microspheres were dispersed in anhydrous ethanol, ultrasonically cleaned, and then vacuum-dried at 40°C until the moisture content of the heat-expandable paraffin-based microspheres was ≤0.05% (w / w); (2) Preparation of ethanol mixture: ethanol and water were mixed at a volume ratio of 9:1 at room temperature, KH-550 was added at 1% of the volume of the mixture, the pH value of the mixture was adjusted to 4, and the mixture was stirred for 1 hour to obtain a silane solution; (3) At room temperature, the heat-expandable paraffin-based microspheres and the silane solution were mixed and stirred at a weight ratio of 1:15 for 6 h to completely suspend the heat-expandable paraffin-based microspheres. The heat-expandable paraffin-based microspheres were then centrifuged and washed with ethanol, and then vacuum-dried at 40°C to obtain heat-expandable paraffin-based microspheres coated with silane coupling agent.

[0025] Preparation Example 2.2 A method for coating the surface of heat-expandable paraffin-based microspheres with a silane coupling agent comprises the following steps: (1) Microsphere pretreatment: The heat-expandable paraffin-based microspheres were dispersed in anhydrous ethanol, ultrasonically cleaned, and then vacuum-dried at 45°C until the moisture content of the heat-expandable paraffin-based microspheres was ≤0.05% (w / w); (2) Preparation of ethanol mixture: ethanol and water were mixed at a volume ratio of 9:1 at room temperature, KH-550 was added at 5% of the volume of the mixture, the pH value of the mixture was adjusted to 5, and the mixture was stirred for 2 h to obtain a silane solution; (3) At room temperature, the heat-expandable paraffin-based microspheres and the silane solution were mixed and stirred at a weight ratio of 1:15 for 6 h to completely suspend the heat-expandable paraffin-based microspheres. The heat-expandable paraffin-based microspheres were then centrifuged and washed with ethanol, and then vacuum-dried at 40°C to obtain heat-expandable paraffin-based microspheres coated with silane coupling agent.

[0026] Example 1 A preparation process of a sponge with adhesive comprises the following steps: S1. Preparation of a colloid mixture: 1 kg of the polyurethane hot melt adhesive obtained in Preparation Example 1.1 and 2.3 kg of ethyl acetate were mixed and mixed using a twin-screw blending method at 50°C for 15 min at a twin-screw speed of 5000 rpm. After uniform mixing, 0.165 kg of the heat-expandable paraffin-based microspheres obtained in Preparation Example 2.1 were added and stirred at 50°C and a twin-screw speed of 5000 rpm for 10 min to obtain a colloid mixture in which the heat-expandable paraffin-based microspheres accounted for 5% of the total amount of the polyurethane hot melt adhesive and ethyl acetate. S2. Place a polyurethane soft foam sponge with a density of 20-40 kg / m3 and a porosity of ≥75% in a vacuum device at a vacuum degree of 0.1 MPa for 15 minutes; S3, completely immersing the polyurethane soft foam sponge obtained in step S2 in the colloid mixture obtained in step S1 for 25 minutes to restore the sponge to a full state; S4. Place the impregnated sponge in a low-temperature oven for drying at a temperature of 50±2°C. After drying for 2 hours, obtain a sponge with glue.

[0027] Example 2 A preparation process of a sponge with adhesive comprises the following steps: S1. Preparation of a colloid mixture: 1 kg of the polyurethane hot melt adhesive obtained in Preparation Example 1.1 and 2.5 kg of ethyl acetate were mixed and mixed using a twin-screw blending method at 60°C for 20 min at a twin-screw speed of 5000 rpm. After uniform mixing, 0.28 kg of the heat-expandable paraffin-based microspheres obtained in Preparation Example 2.1 were added and stirred at 60°C and a twin-screw speed of 5000 rpm for 10 min to obtain a colloid mixture in which the heat-expandable paraffin-based microspheres accounted for 8% of the total amount of the polyurethane hot melt adhesive and ethyl acetate. S2. Place a polyurethane soft foam sponge with a density of 20-40 kg / m3 and a porosity of ≥75% in a vacuum device at a vacuum degree of 0.1 MPa for 18 minutes; S3, completely immersing the polyurethane soft foam sponge obtained in step S2 in the colloid mixture obtained in step S1 for 25 minutes to restore the sponge to a full state; S4. Place the impregnated sponge in a low-temperature oven for drying at a temperature of 50±2°C. After drying for 2 hours, obtain a sponge with glue.

[0028] Example 3 A preparation process of a sponge with adhesive comprises the following steps: S1. Preparation of a colloid mixture: 1 kg of the polyurethane hot melt adhesive obtained in Preparation Example 1.1 and 2.7 kg of ethyl acetate were mixed and mixed using a twin-screw blending method at 70°C for 16 min at a twin-screw speed of 5000 rpm. After uniform mixing, 0.37 kg of the heat-expandable paraffin-based microspheres obtained in Preparation Example 2.1 were added and stirred at 70°C and a twin-screw speed of 5000 rpm for 10 min to obtain a colloid mixture in which the heat-expandable paraffin-based microspheres accounted for 10% of the total amount of the polyurethane hot melt adhesive and ethyl acetate. S2. Place a polyurethane soft foam sponge with a density of 20-40 kg / m3 and a porosity of ≥75% in a vacuum device at a vacuum degree of 0.1 MPa for 15 minutes; S3, completely immersing the polyurethane soft foam sponge obtained in step S2 in the colloid mixture obtained in step S1 for 25 minutes to restore the sponge to a full state; S4. Place the impregnated sponge in a low-temperature oven for drying at a temperature of 50±2°C. After drying for 2 hours, obtain a sponge with glue.

[0029] Example 4 A preparation process of a sponge with adhesive, which is different from Example 2 in that the polyurethane hot melt adhesive uses the polyurethane hot melt adhesive obtained in Preparation Example 1.2, and the heat-expandable paraffin-based microspheres use the heat-expandable paraffin-based microspheres obtained in Preparation Example 2.2. The rest are the same as Example 2.

[0030] Example 5 A preparation process of a sponge with adhesive, which is different from Example 2 in that the polyurethane hot melt adhesive uses unmodified polyurethane hot melt adhesive, and the rest is the same as Example 2.

[0031] Example 6 A preparation process of a sponge with adhesive, which is different from Example 2 in that the heat-expandable paraffin-based microspheres are unmodified heat-expandable paraffin-based microspheres, and the rest are the same as Example 2.

[0032] Example 7 A preparation process of a sponge with adhesive, which is different from Example 2 in that the polyurethane hot melt adhesive and the heat-expandable paraffin-based microspheres are both unmodified polyurethane hot melt adhesive and heat-expandable paraffin-based microspheres, and the rest are the same as Example 2.

[0033] Comparative Example 1 A preparation process of a sponge with adhesive is different from that of Example 2 in that the colloid mixture does not contain heat-expandable paraffin-based microspheres, and the rest is the same as that of Example 2.

[0034] Comparative Example 2 A preparation process of an adhesive sponge is different from that of Example 2 in that the addition amount of heat-expandable paraffin-based microspheres is 3% of the total amount of polyurethane hot melt adhesive and ethyl acetate, and the rest is the same as that of Example 2.

[0035] Comparative Example 3 A preparation process of an adhesive sponge is different from that of Example 2 in that the addition amount of heat-expandable paraffin-based microspheres is 15% of the total amount of polyurethane hot melt adhesive and ethyl acetate, and the rest is the same as that of Example 2.

[0036] Application Examples 1-7 and Comparative Application Examples 1-3 A sponge-leather composite is obtained by compounding the adhesive sponge obtained in the above-mentioned embodiments and comparative examples with leather. The specific compounding process is as follows: plasma-treating the leather surface, subjecting the adhesive sponge to treatments such as freeze-dehumidification, and then stacking the leather with the adhesive sponge with the back side facing down. The leather is placed in a compounding device with a pressure of 0.5 MPa and then subjected to gradient heating. The gradient heating process is as follows: the first step is heating to 80°C for preheating for 3 minutes, the second step is heating to 100°C and maintaining for 5 minutes, and the third step is cooling to 90°C and maintaining for 2 minutes to bond the adhesive sponge to the leather to obtain a leather-sponge composite.

[0037] Performance testing The sponge leather composites obtained in the above application examples and comparative application examples were tested for bonding strength. The testing method was in accordance with the provisions of Method B in GB 8808. The test temperature was 23±2°C, the humidity was 50±10%, the test speed was 100±10 mm / min, and 5 samples were randomly taken in the warp and weft directions, with a sample size of 200 mm×50 mm. The arithmetic mean of the peeling force of the samples in the warp and weft directions was recorded.

[0038] Table 1 Sponge leather composite peeling test results From the table above we can see that: The leather-sponge composites obtained in Examples 1-4 of the present application cannot be peeled off in the radial direction, and the peeling strength in the weft direction is all above 17N. In addition, the surface of the leather-sponge composites obtained in Examples 1-4 of the present application is smooth and wrinkle-free, indicating that the colloid of the adhesive sponge of the present application can flow evenly after heating, thereby achieving uniform bonding and improving the quality of the leather and sponge composite.

[0039] Compared with Application Example 2, when only one of the polyurethane hot melt adhesive and the heat-expandable paraffin-based microspheres is modified or neither is modified, the radial peeling force and the weft peeling force of the sponge leather composite obtained in Application Example 5-7 are significantly reduced compared with Application Example 2. It can be seen that after both the polyurethane hot melt adhesive and the heat-expandable paraffin-based microspheres are modified, the bonding strength between the leather and the sponge can be effectively improved.

[0040] Compared with Application Example 2, when the heat-expandable paraffin-based microspheres are missing, the radial peeling force and the weft peeling force of the sponge leather composite obtained by Application Example 1 are significantly reduced compared with Application Example 2, and the surface of the obtained composite has more wrinkles. The reason is that when the heat-expandable paraffin-based microspheres are missing, the polyurethane hot melt adhesive begins to flow downward under the action of gravity after heating, and only a small amount of adhesive on the surface of the sponge can be compounded with the leather, so the peeling strength between the leather and the sponge is very low, and the composite quality is poor.

[0041] Compared with Application Example 2, when the addition amount of heat-expandable paraffin-based microspheres is lower than the limit of this application, due to the small amount of heat-expandable paraffin-based microspheres, the amount of polyurethane hot melt adhesive that can be lifted and moved upward after heating is small, thereby reducing the colloid content used for bonding, so the peel strength between the leather and the sponge is reduced; when the addition amount of heat-expandable paraffin-based microspheres is too high, the proportion of polyurethane hot melt adhesive in the colloid mixture is reduced, and the colloid content used for your sister Na is reduced, and the peel strength between the leather and the sponge is also reduced. Therefore, when the addition amount of heat-expandable paraffin-based microspheres is limited to 5-10% of the total amount of polyurethane hot melt adhesive and ethyl acetate, the quality of the sponge and leather composite can be effectively improved.

[0042] The embodiments of this specific implementation method are all preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A sponge with adhesive, characterized in that: The adhesive sponge includes a polyurethane soft foam sponge and a colloid mixture immersed in the polyurethane soft foam sponge. The colloid mixture is composed of polyurethane hot melt adhesive, heat-expandable paraffin-based microspheres and ethyl acetate. The weight ratio of the polyurethane hot melt adhesive to ethyl acetate is 1:(2.3-2.7), and the amount of the heat-expandable paraffin-based microspheres is 5-10% of the total amount of the polyurethane hot melt adhesive and ethyl acetate.

2. The adhesive sponge according to claim 1, characterized in that: The polyurethane hot melt adhesive is modified to obtain a modified polyurethane hot melt adhesive, and the modification method comprises the following steps: (1) Add dehydrated diisobutyl sebacate to the dry polyurethane hot melt adhesive at a temperature of 80±2°C and mix and stir under vacuum for at least 30 minutes until no bubbles are generated; (2) Lower the temperature to 60 ± 2 °C, add calcium carbonate, and continue stirring under vacuum for not less than 30 min to obtain a blend; (3) The blend is extruded and dried to obtain a modified polyurethane hot melt adhesive with a particle size of 1-20 μm.

3. The adhesive sponge according to claim 2, characterized in that: The amount of dehydrated diisobutyl sebacate added is 5-10 wt% of the weight of the polyurethane hot melt adhesive, and the amount of calcium carbonate added is 1-3 wt% of the weight of the blend obtained in step (1).

4. The adhesive sponge according to claim 2, characterized in that: The polyurethane hot melt adhesive in step (1) has a melting point of 70-100° C. and a particle size of 80-150 μm.

5. The adhesive sponge according to claim 1, characterized in that: The surface of the thermally expandable paraffin-based microspheres is coated with a silane coupling agent.

6. The adhesive sponge according to claim 5, characterized in that: The method for coating the surface of heat-expandable paraffin-based microspheres with a silane coupling agent comprises the following steps: (1) Microsphere pretreatment: The heat-expandable paraffin-based microspheres were dispersed in anhydrous ethanol, ultrasonically cleaned, and then vacuum-dried at 40-45°C. (2) Preparation of ethanol mixture: at room temperature, ethanol and water are mixed in a volume ratio of 9:1, KH-550 is added at a volume ratio of 1-5% of the mixed solution, the pH value of the mixed solution is adjusted to 4-5, and the mixture is stirred for 1-2 hours to obtain a silane solution; (3) At room temperature, the heat-expandable paraffin-based microspheres and the silane solution were mixed in a weight ratio of 1:15 and stirred until the heat-expandable paraffin-based microspheres were completely suspended. The heat-expandable paraffin-based microspheres were then centrifuged and washed with ethanol. The heat-expandable paraffin-based microspheres were then vacuum-dried at 40°C to obtain heat-expandable paraffin-based microspheres coated with silane coupling agent.

7. A process for preparing the adhesive sponge according to any one of claims 1 to 6, characterized in that: The steps include: S1. Preparation of a colloid mixture: polyurethane hot melt adhesive and ethyl acetate are mixed by a twin-screw blending method at 50-70° C. for not less than 15 minutes, with a twin-screw speed of 5000 rpm or higher. After uniform mixing, heat-expandable paraffin-based microspheres are added, and stirring is continued at 50-70° C. and a twin-screw speed of 5000 rpm or higher for 10 minutes to obtain a colloid mixture; S2. Place the polyurethane soft foam sponge in a vacuum device and vacuum it for no less than 15 minutes; S3, completely immersing the polyurethane soft foam sponge obtained in step S2 in the colloid mixture obtained in step S1, with the immersion time being ≥ 20 min; S4, drying the impregnated sponge to obtain a sponge with glue.

8. The process for preparing the adhesive sponge according to claim 7, wherein: The vacuum degree in step S2 is not less than 0.1 MPa.

9. The process for preparing a sponge with adhesive according to claim 7, characterized in that: The drying temperature in step S4 is 50±2°C.

10. An application of the adhesive sponge according to claim 1 to compound the adhesive sponge with leather, characterized in that: The method comprises the following steps: stacking leather and a sponge with adhesive, placing them in a composite device at a pressure of 0.5 MPa for gradient heating, wherein the gradient heating process comprises the following steps: first, heating to 80°C for preheating for 3 minutes; second, heating to 100°C and maintaining for 5 minutes; and third, cooling to 90°C and maintaining for 2 minutes, thereby bonding the sponge with adhesive to the leather to obtain a leather-sponge composite.

Citation Information

Patent Citations

  • Waterproof composite film for composite fabric

    CN106142695A

  • Method for preparing graphene flame-retardant polyurethane sponge for automobile interior

    CN108774338A

  • Shape-follow-up insole and manufacturing method thereof

    CN109171108A

  • Expandable microspheres with excellent solvent resistance and preparation method of expandable microspheres

    CN109705392A

  • Siloxane modified thermal foaming microsphere, polyacrylate foam as well as preparation method and application of polyacrylate foam

    CN116376094A